Factors Determining Concurrent Reclamation and Abandonment of Cultivated Land on the Qinghai-Tibet Plateau - Yiming Sang; Liangjie Xin (Land, 2023)
The Tibetan Plateau has important functions, such as water and soil conservation, wind and sand control, carbon fixation, and biodiversity protection. Agricultural development on the Tibetan Plateau not only maintains local food security but is also related to the important ecological functions in China and Asia. This study analyzed the spatial distribution of reclaimed and abandoned cultivated land in the Yarlung Zangbo–Lhasa–Nyangqu River (YLN) region on the Qinghai-Tibet Plateau from 2000 to 2020 using high-resolution remote sensing data. Additionally, this study explored the factors influencing spatial distribution patterns using a landscape pattern index and correlation analysis. The results showed that: (1) From 2000 to 2020, cultivated land reclamation and abandonment coexisted in the YLN region. The total areas of reclaimed and abandoned cultivated land were 558.57 and 196.85 km2, and their growth and abandonment rates were 25.47 and 8.29%, respectively. (2) Apparent regional differences existed in the distribution of reclaimed and abandoned lands. The reclaimed land was concentrated in the northeast and southwest of YLN, whereas abandoned land was scattered, with relatively higher fragmentation than in the former. (3) Climate and location affected the spatial distribution of both land types, with precipitation, aspect, and SOM having less influence and temperature, elevation, slope, traffic conditions, and farming radius having relatively prominent influence. (4) Socioeconomic factors were the main factors driving changes in cultivated land area in the region, wherein grain output and the number of livestock positively impacted reclamation and abandonment, relatively more significantly for reclamation. This study helps to understand the land use changes and their impacts in the YLN region on the Qinghai-Tibet Plateau. It is of great significance for formulating appropriate sustainable development strategies and land management policies, and ensuring the sustainable development of local ecological environment and cultivated land resources utilization.